Subjects With Celiac Disease Have Difficulty Determining if They Received Gluten in a Randomized Double Blind Placebo Controlled Gluten Challenge: 1147 - Cartee, Amanda; Van Dyke, Carol; Chadrick, Hinson; Katherine, King; Horwath, Irina; Marietta, Eric; Choung, Rok Seon; Murray, Joseph (The American journal of gastroenterology, 2018)
Introduction: A gluten free diet (GFD) is the only treatment for celiac disease (CD). Most patients with CD rely on symptoms as an indicator of gluten exposure. Methods: Subjects (n=28) were recruited for a randomized double blind placebo controlled gluten challenge. Fourteen subjects had CD on a GFD for at least 2 years. Healthy subjects (n=14) were on a gluten-containing diet and did not have a CD family history. Subjects within each group were block randomized to receive either 6 grams of gluten or placebo suspension. Investigators were blinded. Subjects completed a 100 mm visual analog symptom questionnaire (nausea, bloating, abdominal pain, and fatigue) at baseline, every 30-60 minutes for 6 hours, and then daily for 3 days. A 10 mm increase or decrease was considered a change. Subjects were asked at each time point if they believed they received gluten. Results: Ten CD subjects were female. Median time on a GFD was 7 years, range 3-29. There was no difference in symptoms between the suspension groups at baseline. Six CD subjects who received gluten had a symptom score change. The median time to symptom onset was 105 minutes. Nausea and abdominal pain were most common. One CD subject was completely asymptomatic. There was no statistical difference in symptoms between the suspensions in the CD group. Only 2/7 CD gluten subjects ever correctly identified the suspension. One subject waited 24 hours before deciding while another indicated "no" "no" and "not sure" sporadically throughout the study. CD subjects who received placebo typically showed some uncertainty too, especially during the day of the challenge, however only 1/7 believed they received gluten at nearly all time points asked. Six controls were female. Some healthy subjects (n=4) noted fatigue after challenge, although not significant compared to placebo. Among those receiving gluten, controls had lower nausea and abdominal pain scores, p=0.005 and 0.21, respectively. Four healthy controls correctly determined gluten suspension. Conclusion: Symptoms are a subjective assessment of possible gluten exposure. Due to their subjective and non-specific nature and no statistical difference in symptoms in CD subjects receiving gluten or placebo, symptoms as a means to determine gluten exposure are largely unreliable. Objective means to identify gluten-related symptoms are needed and may be helpful in clinical practice for patients with celiac disease experiencing ongoing gastrointestinal symptoms.